Creative Biblio-Counseling to Enhance Adversity Quotient of Juvenile Prisoners - Puji Gusri Handayani; Hafiz Hidayat; Rahmi Dwi Febriani; Soeci Izzati Adlya; Shaamilah Binti Shahabuddin (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
The adversity quotient has an important role in an individual's life. By having a high adversity quotient, individuals will be able to overcome the difficulties faced. Juvenile prisoners are individuals who require special attention in an effort to improve their quotient of adversity to avoid becoming recidivists. This study aimed to test the effectiveness of creative biblio-counselling to improve the adversity quotient of juvenile prisoners. This study used a pre-experimental design with pre-test and post-test designs. The population in this study was 50 child prisoners, then 8 juvenile prisoners selected using purposive sampling techniques. The research instrument is the profile adversity quotient modification scale which has a high level of reliability and validity. The data analysis used is the Wilcoxon test. The results showed that the adversity quotient of juvenile prisoners increased after creative biblio-counseling treatment. Therefore, based on the findings of this study, counselors at LPKA can apply creative biblio-counseling using books, videos, and films to improve the adversity quotient of juvenile prisoners and as a basis for supporting adolescent development tasks.